Postcolonial Feminisms and Introducing Sociology in the Imperium - Puri, Jyoti (Radical Teacher, 2015)
This article addresses the limits of teaching sociology as a Eurocentric modernist discipline in the context of the postcolonial present. Living in a transnational and globalized world makes the most basic and fundamental sociological concepts woefully delimiting, since they are ahistoricized and universalized terms rooted in a very specific modernist life-world. Words such as ‘individual,’ ‘self,’ ‘society,’ and ‘social’ are used routinely in everyday parlance as if their meanings are self-evident. This is not surprising given that scholarship and undergraduate teaching in the United States have also rendered them as generic, self-evident words without unraveling them reflectively as concepts, much like the ways in which ‘nation,’ ‘state,’ ‘gender,’ ‘race,’ ‘ethnicity,’ ‘sexuality,’ ‘citizen,’ ‘immigrant,’ ‘migrant,’ and ‘other,’ have been shown to reflect particular modern, liberal understandings. What scholarly, disciplinary and pedagogical challenges are faced when notions such as the ‘individual’ and ‘self’ are interrogated in the classroom from transnational and postcolonial perspectives? Writing from the standpoint of an immigrant feminist sociologist teaching in liberal arts colleges in northeast United States, I reflect on strategies that draw students toward a critical engagement with sociology while coming to grips with subject positions and political and cultural histories that shape such engagements.